Exploiting low-grade waste heat to produce electricity through supercapacitor containing carbon electrodes and ionic liquid electrolytes. (20th January 2022) - Haque, Mazharul; Abdurrokhman, Iqbaal; Idström, Alexander; Li, Qi; Rajaras, Azega; Martinelli, Anna; Evenäs, Lars; Lundgren, Per; Enoksson, Peter
Highlights: Thermal energy is utilized to store electricity in supercapacitors without a fixed temperature gradient. Observed voltage output originates from the thermocapacitive effect. 947 mV voltage is recovered in a stacked system with two devices in series. Asymmetry in the interfaces originates from different diffusivity of ions in ionic liquids. Energy harvesting and storage in a single multitasking device opens up a parallel life to SCs. Abstract: Low-grade thermal energy harvesting presents great challenges to traditional thermoelectric systems based on the Seebeck effect, the thermogalvanic effect, and the Soret effect due to fixed temperature gradient and low voltage output. In this study, we report an ionic thermoelectric system, essentially a supercapacitor (SC) containing an ionic liquid (IL) electrolyte and activated carbon electrodes, which works on the thermocapacitive effect and does not require any fixed temperature gradient, rather it works in a homogeneously changing temperature. A systematic investigation is carried out on SCs containing two different ILs, 1-Ethyl-3-methylimidazolium bis (trifluoromethylsulfonyl), EMIm TFSI, and 1-Ethyl-3-methylimidazolium acetate, EMIm OAc. A high voltage output of 176 mV is achieved for EMIm TFSI containing SC by exposing just to 60 °C environment. Moreover, a large voltage of 502 mV is recovered from the SC upon subjecting to heat after one electrical charge/discharge cycle. A system containing two SCs in series demonstrates a significant voltage of 947 mV. The observed performance difference between the two ILs is rationalized in terms of the extent of asymmetry in the interfaces of the electrical double layer that essentially originates from different diffusivity of individual ions. The mechanism can be applied to a plethora of ILs to exploit low-grade heat to store electricity without a fixed temperature gradient, opening up the possibility to merge different scientific communities and enrich this rising research field.